Context-based interoperability of semantic web services. (18th May 2019) - Mecheri, Karima; Boufaida, Mahmoud; Meslati, Djamel; Souici-Meslati, Labiba
Semantic mediation is a necessary mechanism to ensure interoperability of web services. In this paper, we present a classification and comparison of works in this field. We propose a semantic model to explicitly describe the heterogeneities of web services. This model is the basis for the mediation automation. In particular, we describe the behavioural semantic sub-model, for which we use the abstract state machine's method and the notion of behavioural context that we have defined. The mediation process we propose is implemented using web services. The core of this implementation is situated in the semantic transformations module, which is based on the mapping of ontologies and the reasoning about these mappings.